Effect of Slime Layer on the Anode Potential in Nickel Matte Electrorefining - T. Innmi (The Minerals, Metals and Materials Society, 1988)
The potential of the nickel matte anode was measured during the matte electrolysis in the commercial cell. The slime layer consists of elemental sulfur and was found to greatly influence the potential of anode. The measurements of porosity and permeability of the slime suggest that the voltage drop of the slime layer dominates the potential. Furthermore, the diffusion of the electrolyte through the slime layer is also one of the factors to determine the potential. In addition, the copper content of the nickel matte anode was found to affect the change in the anode potential during the electrolysis. The role of copper on the anodic dissolution of nickel matte is discussed in this work.